A field experiment on surface wave isolation by partially embedded periodic pile barriers. (February 2023) - Liu, Yan-Zhao; Yu, Si-Shun; Liu, Ze; Yu, Gui-Lan
The bandgap characteristics of periodic structures show a great application prospect in seismic isolation and vibration mitigation. A T-shaped partially embedded periodic pile barrier is designed and studied based on the Bloch's theorem. The proposed structure is fabricated and tested in field experiment to validate the simulation and the isolation performance. Good agreements are observed between the measured and the corresponding simulated results which present effective isolation for surface waves. The influences of the embedded length in the soil and the arrangement of the pile are investigated. The results show that the embedded length is the key parameter affecting the vibration attenuation. The smaller the embedded length, the lower the frequency of attenuation zone, and thanks to the embedded length; the proposed barrier exhibits better performances than the fully embedded and non-embedded barriers in maximum bandgap width, tunability, and feasibility in engineering. Gradient distribution of the embedded length leads to a wider frequency range of attenuation.